Hidden under ice and mud: diversity of shell-bearing microgastropods in the eastern Arctic seas. Issue 8 (16th July 2020) - Nekhaev, Ivan O.; Krol, Ekaterina N.
Abstract : The arctic environment continues to undergo a rapid transformation due to climatic shifts, human activities, and invasive species. Revealing ecosystem responses to these stressors requires extensive knowledge about the diversity of the Arctic fauna and flora. Gastropoda is one of the most diverse invertebrate groups within the marine benthos. Shell-bearing microgastropods (snails no larger than 5 mm) represent a significant part of gastropod diversity but remain among the most poorly studied marine animals worldwide. The aim of the present review is to summarize the existing data on diversity and distribution of shell-bearing microgastropods in the eastern Arctic seas. Currently, 66 species of shell-bearing microgastropods belonging to 17 families are known from the region. The taxonomy of snails is still based mainly on shell characters. Molecular phylogenetic analysis still has not been used in the taxonomy of microgastropods from the eastern Arctic. The Barents Sea is the most species-rich region with 51 microgastropod species. The diversity in the other seas is significantly lower, from 10–20 species, and only 9 species in the case of the open Arctic basin. Analysis of functional traits revealed three groups of microgastropods: coastal species feeding on algae and detritus, shelf species feeding on foraminiferans, and parasitic/symbiotic species. Abundance of shell-bearing microgastropods can be high, especially in coastal environments, where micromolluscs may be the most numerous among all the macroinvertebrates. Some limitations for studies of microgastropods in the Arctic are reviewed.